EU’s Carbon Border Adjustment Mechanism: Assessment of Future Payments for Exporters - Sergei S. Sudakov; Samvel S. Lazaryan; Anton I. Votinov (Финансовый журнал, 2022)
Starting in 2026, the EU will introduce the Carbon Border Adjustment Mechanism (CBAM). Under this mechanism imports of certain products to the EU will be subject to a special fee based on the carbon intensity of these goods. This article is devoted to the quantification of payments under this mechanism for several countries in the Eurasian region: the EAEU member states, Georgia, Tajikistan and Uzbekistan. These countries were chosen due to the relatively high share of the EU in their exports. CBAM payments have a dynamic nature because certain parameters of the mechanism vary on an annual basis under the influence of a number of factors, for example, due to the annual change in the CBAM rate. According to the estimates obtained, the lowest aggregate CBAM payment accrues to imports from Armenia to the EU. Between 2026 and 2035 it is estimated 95.8 million euros (single CBAM pass-through rate into final prices in EU). The largest payment is estimated to come from Russia: it amounts to 97 billion euros over the same period (zero CBAM pass-through rate). The largest share of payments in exports to the EU is observed for Uzbekistan, Georgia, Tajikistan and Belarus. The largest share of payments falls on imports of metals (ferrous and non-ferrous), fertilizers, electricity and oil. However, the conclusion on products requires additional verification, since for a number of countries in the Eurasian region there are no high-quality and detailed data on the carbon intensity of certain goods.